Bioprospecting of native algal strains with unique lipids, proteins, and carbohydrates signatures: A time dependent study. Issue 2 (10th August 2021) - Samadhiya, Kanchan; Ghosh, Atreyee; Kashyap, Mrinal; Anand, Vishal; Bala, Kiran
Abstract: Aim of this study is uncovering potential strains of microalgae from Indore, Madhya Pradesh situated in central India with a diverse climate for sustainable production of different bio‐products. Assessing the entire biochemical profile is crucial to select species‐ specific metabolites for sustainability of algal bio‐refinery processes. In the current study, seven algal species ( C. proboscideum, Desmodesmus psuedocommunis, Asterarcys quadricellulare, Ettlia texensis, Pediludiela daitoensis, Coelastrella sp., Pectinodesmus sp.) were isolated and identified using Internal Transcribed Spacer (ITS) and 18 s rRNA sequences, and these species found to be from the Chlorophyta phylum. The highest biomass productivity (51.25 ± 1.96 μg/ml/day) with chlorophyll content (33.07 ± 0.63 μg/ml) was observed in A. quadricellulare on 21st day ( P < 0.0001). Biochemical profiling of isolated species showed each species is unique in its biochemical composition (total lipids, carbohydrates, and proteins). Coelastrella sp. and Pectinodesmus sp. was found to be accumulating considerable quantities of ( P < 0.0001) carbohydrates (303.3 ± 1.11 μg/mg dry cell weight) and lipids (212.67 ± 2.53 μg/mg per dry cell weight), respectively. Whereas P. daitoensis was found best ( P < 0.0001) for protein production (205.78 ± 2.56 μg/mg dry cell weight), on 21st day. Highest total fatty acid content was detected in Pectinodesmus sp. (115.74 μg/mg) on 21st day, which has shown good saturated fatty acid (SFA) and mono unsaturated fatty acid (MUFA) percentage, inflicting high quality biodiesel production. Confocal microscopy further supported the data. Assessing the biochemical profile at different phases of growth for each species therefore reduce the production time of biofuels as well as make this process much more cost‐effective.